Inhibition of in Vitro Pollen Tube Growth by Isolated S-Glycoproteins of Nicotiana alata. - Jahnen, W. (1989)
Pollen from three S-genotypes of Nicotiana alata was grown in vitro in the presence of S-glycoproteins isolated from styles of the same three genotypes. Pollen germination was not affected by the presence of the S-glycoproteins, but pollen tube growth of all genotypes was inhibited. S2 pollen was preferentially inhibited by the S2-glycoprotein and S3 pollen by the S3-glycoprotein. The S6-glycoprotein preferentially inhibited growth of both S2 and S6 pollen over S3 pollen. Heat treatment dramatically increased the inhibitory activity of the S-glycoproteins as inhibitors both of pollen germination and tube growth; after heat treatment, S-allele specificity of pollen tube inhibition was not detected.